Estrategias de marketing para incrementar el nivel de ventas de la comercial Avieros en la ciudad de Huamachuco. - Campos Baltazar, Violeta Enedina (2014)
The present work of investigation was elaborated by the purpose of increasing the level of sales of the distribution Company Avieros in Huamachuco. With the determination of this work, the company will put emphasis in the most relevant points at which not they being employed correctly, allowing to determine the strategies of marketing. For the present research report the design was in use descriptive - transeccional, statistician; and a survey was applied as technology of investigation. In the surveys applied to the clients of the distribution Company Avieros in Huamachuco, we can highlight that the Strategies of marketing it influences the ventas of the Company doing that this one is the most profitable. As conclusion of the same one it hopes that the production of this work is of great usefulness to make to be aware to the owners of the company so that in a managerial highly competitive environment, the strategies of Marketing it constitutes a necessary tool to achieve the aim of the Company and development in the company from a clear definition of his managerial philosophy.